"Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Papan Kompetisi Bangun Datar (Pakom Bantar) TerhadapPemahaman KonsepMatematika" - Erna Fitria Ningrum (Prosiding University Research Colloquium, 2021)
The The purpose of this study was to determine the effect of the Problem BasedLearning model assisted by the flat wake competition board media on theunderstanding of Mathematical concepts for fourth grade students at Banaran 2 StateElementary School. This research is a type of Pre-Experimental Design research, withthe One Group Pretest-Posttest Design model. Samples had taken as many as 20students used as an experimental class. The sampling technique used saturatedsampling. Data collection used the test method. This test is used to test the extent towhich students experience changes in understanding of Mathematical concepts beforeand after being treated. The analysis used in this study is the Wilcoxon Signed RankTest with SPSS version 23.0. The results showed the Problem Based Learning modelassisted by the flat wake competition board media influense the understanding ofMathematical concept. Evidence of an increase in students understanding ofMathematical concept is a significant difference between the pretest score and theposttest score, the average pretest score 0f 60.71 while the posttest score is 76.60. Thisis supported by the existence of a hypothesis test conducted with the Wilcoxon SignedRank Test, the Asymp. Sig. (2-tailed) of 0.000 (0.000 < 0.005). based on the results ofthe analysis and discussion there was an increase of 15.89 from the average results ofthe preest and posttest. The results of this research can be concluded that the use ofProblem Based Learning model assisted by the flat wake competition board media hasa significant effect on the understanding of Matematical concepts on the theorycircumference and area of a flat shape.